An Improved Face Recognition Method Based on Convolutional Neural Network - Syed Muhammad Daniyal; Atiya Masood; Mansoor Ebrahim; Syed Hasan Adil; Kamran Raza (JISR on Computing, 2024)
Face recognition using an image-processing technique is a valuable and effective approach to verifying the identity of a human being. Authorizing users based on human face identification remains one of the biggest challenges. However, with the improvement of deep learning and the creation of deep convolutional neural networks, the performance of face recognition has significantly improved. However, the outcomes from different models and networks are quite different in terms of accuracy. This paper proposes a face recognition model based on a Convolutional neural network (CNN). The recognition rate of the AT&T and AR data set on the proposed model is 99.17% and 99.12%.